Marketing (IntechOpen, 2023)
This book on marketing continues to reflect our firm belief that the Wheel of Consumer Analysis is a powerful tool not only for organizing consumer behaviour knowledge but also for understanding consumers and for guiding the development of successful marketing strategies. In fact, it has been used by marketing consultants and practitioners to do so. The various chapters presented here follow several approaches, which researchers can explore in different contexts. This book intends to contribute to a better understanding of the application areas of marketing strategies and shows how these business practices in social sciences can stimulate various topics.